2020
DOI: 10.4269/ajtmh.20-0089
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Epidemic Cholera in Lusaka, Zambia—2017

Abstract: On October 6, 2017, the Zambia Ministry of Health declared a cholera outbreak in Lusaka. By December, 1,462 cases and 38 deaths had occurred (case fatality rate, 2.6%). We conducted a case-control study to identify risk factors and inform interventions. A case was any person with acute watery diarrhea (³ 3 loose stools in 24 hours) admitted to a cholera treatment center in Lusaka from December 16 to 21, 2017. Controls were neighbors without diarrhea during the same time period. Up to two controls were matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In urban Bangladesh, investigators followed household contacts of persons with recent cholera and observed that contacts who drank stored household drinking water that contained V. cholerae had an 8.6-fold increase risk of cholera . Another study in Zambia during a cholera outbreak in 2017 found that sharing a pit latrine with a patient with cholera increased the odds of becoming infected by 4-fold . Fecal shedding of V. cholerae in the household may also contribute to an increased risk of infection.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In urban Bangladesh, investigators followed household contacts of persons with recent cholera and observed that contacts who drank stored household drinking water that contained V. cholerae had an 8.6-fold increase risk of cholera . Another study in Zambia during a cholera outbreak in 2017 found that sharing a pit latrine with a patient with cholera increased the odds of becoming infected by 4-fold . Fecal shedding of V. cholerae in the household may also contribute to an increased risk of infection.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…93 Another study in Zambia during a cholera outbreak in 2017 found that sharing a pit latrine with a patient with cholera increased the odds of becoming infected by 4-fold. 94 Fecal shedding of V. cholerae in the household may also contribute to an increased risk of infection. Infected household contacts in Bangladesh were found to shed for an average of 2 days, and in households where a person shed V. cholerae for 4 days or more, a higher likelihood of infection in other household members was observed.…”
Section: ■ Environmental Risk Factorsmentioning
confidence: 99%
“…This trend has been observed in Zambia, Nigeria, Zimbabwe, Tanzania, Kenya, and other countries. 14,[34][35][36] Finn and Cobbinah drew attention to the interface between informality in urban settlements and climate change and how these can potentiate each other. 37 This further increases the risk of cholera outbreaks in urban slums.…”
Section: Why Is Africa Unable To Prevent Cholera Outbreaks From Occur...mentioning
confidence: 99%
“…10 Risk factors for transmission of the disease include, among others, consumption of contaminated water or food, lack of access to safe sanitation, inadequate handwashing, especially after using the toilet, increased rainfall, flooding, and lack of good drainage. [11][12][13][14][15][16] Outbreak prevention and control are through the provision of adequate quantities of safe drinking water and improved sanitation to affected populations, enhancing personal hygiene and clinical management of cases. An oral cholera vaccine has been introduced and rolled out widely to prevent the spread of ongoing epidemics to unaffected areas and prevent epidemics in humanitarian settings.…”
Section: Introductionmentioning
confidence: 99%
“…Cholera outbreaks occur when potable water is unavailable and basic hygiene is poor. In total, 34,950 cases of cholera were reported in Zambia between 2008 and 2017, and the country is considered endemic for cholera with crowded urban areas at highest risk [13,32,33]. Respiratory and diarrheal diseases, among the leading causes of death in Zambia, particularly in children, along with common parasitic infections of the gut [34], can be prevented with handwashing, water chlorination, and periodic household anti-helminthic treatment [35][36][37][38][39][40][41][42][43].…”
Section: Impact Of the Ghp Intervention On Sharing Household Duties (...mentioning
confidence: 99%